Pembelajaran Bahasa Arab Berbasis Pendekatan Berdiferensiasi pada Kurikulum Merdeka - Weri, Weri Yanto; Yuniar, Yuniar; Qaaf, Muhammad Al Fath; Ramadhan, Muhammad Kevin; Jannah, Miftahul (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study analyzes the implementation of differentiated instruction in Arabic language learning at SMK N 1 Penukal. Using a descriptive qualitative method, this research identifies students' learning styles visual, auditory, and kinesthetic as the basis for designing instructional strategies. Among 33 students, 12 have a visual learning style, 10 are auditory learners, and 11 are kinesthetic learners, allowing learning groups to be structured according to their respective needs. Lesson planning begins with a diagnostic assessment to determine students' learning profiles. Teaching modules are designed with varied strategies, such as infographics and concept maps for visual learners, group discussions and audio recordings for auditory learners, and simulations and role-playing for kinesthetic learners. The learning process incorporates differentiation in content, process, and product. Evaluation is conducted through creative projects, oral presentations, and portfolio-based assignments aligned with students' learning styles. The findings indicate that differentiated instruction enhances students' motivation and academic achievement. However, challenges such as limited facilities and time management in assessments still need to be addressed. School support, including the Guru Penggerak training program and In-House Training (IHT), plays a crucial role in successfully implementing this strategy. This study contributes to the development of a differentiated Arabic language learning model and can serve as a reference for other educational institutions in implementing the Merdeka Curriculum